Local and Remote Postconditioning Decrease Intestinal Injury in a Rabbit Ischemia/Reperfusion Model - Mu Yang; Jian-Xin Dong; Lu-Bin Li; Hai-Jie Che; Jun Yong; Fu-Bo Song; Tao Wang; Jv-Wen Zhang (Gastroenterology Research and Practice)
Intestinal ischemia/reperfusion (I/R) injury is a significant problem that is associated with high morbidity and mortality in critical settings. This injury may be ameliorated using postconditioning protocol. In our study, we created a rabbit intestinal I/R injury model to analyze the effects of local ischemia postconditioning (LIPo) and remote ischemia postconditioning (RIPo) on intestinal I/R injury. We concluded that LIPo affords protection in intestinal I/R injury in a comparable fashion with RIPo by decreasing oxidative stress, neutrophil activation, and apoptosis.